An investigation into the extent of gender responsiveness of the student accommodation environment and policy at Midlands State University, Zimbabwe - Chauraya, Efiritha (University of Zimbabwe, Human Resources Rresearch Centre (HRRC), 2016)
The study explored the extent of gender responsiveness of the Midlands State University (MSU) accommodation facilities. Keta areas covered by the research questions were: the gender provisions of the MSU accommodation policy and the gender implication of the adequacy, security, privacy and reliability of the accommodation facilities. The case study research design was used and the research instruments used wee interviews, questionnaires and an exploratory inspection. The MSU students who were in residence during semester one of 2006 formed the population of the study. The study findings revealed that though the MSU has the basic accommodation infrastructure that an ordinary university should have, the facilities need additional support to make them gender responsive. The study confirmed that the accommodation policy was gender-blind and implementation of the policy on the ground was somewhat gender neutral. Against this background this paper advances recommendations to strengthen the university commitment and action on gender responsiveness of its accommodation policy and environment. Key among them is: the need by the university to mainstream a gender perspective in the existing accommodation policy; the need to expand, maintain, redesign and refurbish existing structures to cater for gender specific needs of the students and also ensure a continuous flow of water in the toilets as well as ensuring that male/female hostel allocation is gender aware.